Gliding for Olympic success - Heck, A.; Uylings, P. (Physics Education, 2022)
When thinking about Olympic winter sports and watching events on television, people mostly focus on events where the chances of success are high for fellow-countrymen. For example, in the Netherlands speed skating is considered the main winter sports event. But with Kimberley Bos there is now also a Dutch medal candidate for the Winter Olympics 2022 in the skeleton discipline. Where speed skaters prepare in summer for the winter season with roller skates, Bos trains on an athletics track with a self-built board on wheels as a replacement for the skeleton. British athletes on the other hand can choose the bobsleigh and skeleton push-start track at the University of Bath for their summer preparation. We prepare for the upcoming Winter Olympics 2022 by taking a physics view on advanced sleighing. We show how school physics helps understanding the motion of athletes in bobsleigh and skeleton and increases respect for the athletes` performance.